Oil stabilization of natural peanut butter using food grade polymers. (December 2016) - Tanti, Rachel; Barbut, Shai; Marangoni, Alejandro G.
Abstract: The application of freeze dried hydroxypropyl methylcellulose (HPMC) and methylcellulose (MC) as stabilizers in peanut butter were investigated. These cellulose derivatives were dispersed in water and subsequently freeze dried and chopped to produce a stabilizer that is able to absorb high amounts of oil. Without this templating approach, HPMC and MC had no effect on peanut butter stability and texture. An alternative spray drying approach was attempted, however, it was found that high incorporation levels were required to have any stabilizing effect, which is undesirable. Centrifugal accelerated stability testing showed a significant reduction in oil leakage for samples stabilized with freeze dried HPMC and MC at addition levels as low as 0.2 wt% in peanut butter, while at addition levels of 2.2 wt%, no oil loss was observed. With the addition of >1 wt% HPMC/MC, peanut butters were shelf stable for 6 months or longer. Textural quality of the peanut butter was investigated using a penetration test. Addition of freeze dried HPMC/MC increased sample firmness and adhesiveness which mimicked the properties of traditional peanut butter products stabilized with hydrogenated vegetable oils. Light and scanning electron micrographs showed morphology differences among the stabilizer preparation methods and minimal structural changes in stabilized peanut butter samples. These experiments helped gain insight into the mechanism of oil entrapment and demonstrated the potential of these food-grade polymers as stabilizers in food systems. Graphical abstract: Highlights: Freeze dried HPMC and MC improved oil stability and texture of natural peanut butter. Peanut butters were shelf stable for 6 mo. or longer with >1 wt% HPMC or MC. HPMC morphology dictated oil holding capacity; stability was achieved by entrapment.